Diagnosis of safety in forest harvesting operations from company records, official databases and land surveys. Improvement action plan - Albizu Urionabarrenetxea, P. M.; Tolosana Esteban, E.; Ulecia Zaldívar, J.; Fernández Carretero, M. (Forest Systems, 2010)
From 1995, Spanish safety legislation has been adapted to the International framework. However, operationally the situation is not so good, at least in the wood harvesting activity. Some forest workers are still found not wearing the compulsory safety equipment, working without respecting safety rules and references to high accidents rates are frequent. To assess those aspects, firstly some comparisons have been made between the accident records in a reference company and the accident indexes at national and regional level for building and farming activities. Secondly, using a purpose-designed questionnaire applied to 35 logging worksites in Castilla y Leon Region, deficiencies in prevention have been identified. The relation between the accident reduction and the prevention methods used by the reference studied company has been confirmed. Also the main causes of the accidents have been analysed. Finally, some recommendations to reduce the risk of accidents in harvesting operations are provided. The main conclusion confirms that the possibility of reducing the accident risk is conditioned to the commitment of all the staff of the timber harvesting company, at every level of responsibility, to search for excellence in safety as one more entrepreneurial goal. This fact should be accompanied by the staff early training and the adequate motivation means.